1993
DOI: 10.1017/s0950268800057095
|View full text |Cite
|
Sign up to set email alerts
|

Distinct yearly change of serotype distribution of human rotavirus in Thailand as determined by ELISA and PCR

Abstract: SUMMARYA total of 241 group A rotavirus-positive stool samples collected from diarrhoeic patients in Thailand between July 1988 and June 1991 were characterized for their serotypes by enzyme-linked immunosorbent assay (ELISA) using serotype-specific monoclonal antibodies and by a polymerase chain reaction (PCR). In July 1988-June 1989, serotype 1 was the most prevalent (63-4%), followed by serotype 4 (1IO0%) and serotype 2 (8-5 %). In July 1989-June 1990, 59-8 % were serotype 1, 24-3 % were serotype 2, and 6 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…Regarding the G type distribution in Thailand, a yearly change in the distribution of the G type was also found in previous studies [Pongsuwanna et al, 1989[Pongsuwanna et al, , 1993. In 1988-1989, 1989-1992, G1 was most prevalent.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regarding the G type distribution in Thailand, a yearly change in the distribution of the G type was also found in previous studies [Pongsuwanna et al, 1989[Pongsuwanna et al, , 1993. In 1988-1989, 1989-1992, G1 was most prevalent.…”
Section: Discussionsupporting
confidence: 76%
“…In 1988-1989, 1989-1992, G1 was most prevalent. In 1990and 1992-1993 and G2 were predominant, respectively. Thus, following the previous studies, a 19-year survey of the distribution of the G type in Thailand was carried out.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in multiple studies both techniques have shown variable sensitivity and specificity with a risk of misdiagnosis 13,14 . Polymerase Chain Reaction (PCR) has become the preferred method for human rotaviruses detection as well as genotype characterization in epidemiologic studies 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A partir desse relato, diversos estudos descreveram a presença desses vírus em diferentes espécies de mamíferos: ratos (PEREIRA et al, 1988b;FREGOLENTE et al, 2009), bovinos (VANOPDENBOSCH & WELLEMANS, 1989GHOSH et al, 2009;BUZINARO et al, 2003;MALIK et al, 2011), búfalos (MONDAL et al, 2013MALIK et al, 2011), suínos (GATTI et al, 1989LUDERT et al, 1991;PONGSUWANNA et al, 1996;BÁNYAI et al, 2008), cavalos (BROWNING et al, 1991), coelhos (GALLIMORE et al, 1993;LUDERT et al, 1995), tamanduá bandeira (HAGA et al,1999), jumento, orangotango e tatu (MASACHESSI et al, 2007), macacos (WANG et al, 2012), leão (WOO et al, 2012;GILLMAN et al, 2013), puma, jaguar e gato (GILLMAN et al, 2013). Em aves, PBV já foi detectado em galinhas (LEITE et al, 1990;SILVIA et al, 2014), frangos de corte (TAMEHIRO et al, 2003), gansos (MASACHESSI et al, 2007), ema, pelicano e faisão (MASACHESSI et al, 2007); em répteis, PBV já foi encontrado em diferentes espécies de cobras (MASACHESSI et al, 2007 (PEREIRA et al, 1988a); na Itália, de 0,42% (CASCIO et al, 1996) e na Argentina, de 0,09% (GIORDANO et al, 2008).…”
Section: Epidemiologia E Patogeniaunclassified